Principles of neural science - Kandel, Eric R.; Schwartz, James H. (James Harris), 1932-2006; Jessell, Thomas M. (New York : McGraw-Hill, Health Professions Division, 2000)
Now in resplendent color, this new edition continues to define the latest in the scientific understanding of the brain, the nervous system, and human behavior. Each chapter is thoroughly revised and includes the impact of molecular biology in the mechanisms underlying developmental processes and in the pathogenesis of disease
Ch. 54. The guidance of axons to their targets -- Ch. 55. The formation and regeneration of synapses -- Ch. 56. Sensory experience and the fine-tuning of synaptic connections -- Ch. 57. Sexual differentiation of the nervous system -- Ch. 58. Aging of the brain and dementia of the Alzheimer type -- Ch. 59. Language and aphasias -- Ch. 60. Disorders of thought and volition: schizophrenia -- Ch. 61. Disorders of mood: depression, mania, and anxiety disorders -- Ch. 62. Learning and memory -- Ch. 63. Cellular mechanisms of learning and the biological basis of individuality
Keywords: Nervous System Diseases; Central Nervous System -- physiology; Mental Processes -- physiology; Neuropsychology